2010
DOI: 10.1161/hypertensionaha.110.159194
|View full text |Cite
|
Sign up to set email alerts
|

Renal Dysfunction Does Not Affect the Peripheral-to-Central Arterial Pressure Transfer Function

Abstract: Abstract-Arterial generalized transfer functions (GTFs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…34 Indirect estimation of the central pressure parameters from the radial waveform using a generalized transfer function could have potentially influenced the present results, but recent studies have demonstrated that the central pressure derived with this method corresponds well with the measured carotid pressure and that the transfer function is generalizable to patients with various degrees of renal function. 43 Antihypertensive medication (including RAS inhibitors and other drug classes) might also have had some influence on the present results through its direct and indirect actions on the renal hemodynamics, although the potential confounding influence was statistically eliminated. Furthermore, in addition to the arterial factors (including arterial pressure, stiffness, and diameter), the venous factors (particularly venous compliance) may also participate in renal hemodynamics.…”
Section: Discussionmentioning
confidence: 81%
“…34 Indirect estimation of the central pressure parameters from the radial waveform using a generalized transfer function could have potentially influenced the present results, but recent studies have demonstrated that the central pressure derived with this method corresponds well with the measured carotid pressure and that the transfer function is generalizable to patients with various degrees of renal function. 43 Antihypertensive medication (including RAS inhibitors and other drug classes) might also have had some influence on the present results through its direct and indirect actions on the renal hemodynamics, although the potential confounding influence was statistically eliminated. Furthermore, in addition to the arterial factors (including arterial pressure, stiffness, and diameter), the venous factors (particularly venous compliance) may also participate in renal hemodynamics.…”
Section: Discussionmentioning
confidence: 81%
“…The estimation of left ventricular remodeling by aortic characteristic impedance using applanation tonometry has been reported to be reliable when compared with magnetic resonance imaging [41]. Furthermore, Payne et al [42] showed that pulse wave analysis transfer functions are reliable in patients with variable degrees of renal dysfunction. Aortic characteristic impedance is related to left ventricular hypertrophy and geometry independent of the level of BP within hypertensive subjects [21].…”
Section: Discussionmentioning
confidence: 99%
“…The former is commercially available and more widely used. Though still debated 22 ) , a generalized transfer function is considered valid for normal subjects, for patients with various diseases 18 , 23 , 24 ) , during exercise 25 ) , during pharmacological intervention 26 ) , and during the Valsalva maneuver 18 ) . The synthesized aortic waveform is normally calibrated with brachial diastolic BP and MAP to obtain central BP; MAP is calculated from the area under the radial waveform on the basis that the radial and brachial waveforms are deemed to be identical 8 ) .…”
Section: How Is Central Bp Measured?mentioning
confidence: 99%